The Culture of Resource Production and the Production of Cultural Resources: A Preliminary Conceptual Reflection on Cultural Resource Management Pandemic Era - Ristiawan, R. Rucitarahma (Gadjah Mada Journal of Tourism Studies, 2024)
The majority of critical cultural tourism studies posit that commodification is a pragmatic process that detaches the essence of cultural property from its proprietors, even if there is no clear ontological demarcation in defining how something appears as culture and cultural resources. This paper aims to elucidate the potential re-conceptualization scheme of cultural resource management by analyzing the emergence of the cultural tourism crisis in the COVID-19 pandemic era through the adoption of the production of nature approach in the critical Marxist study. This paper commences with a preliminary explanation of the process by which cultures are perpetually produced and reproduced by society, thereby becoming a component of nature. This paper also considers the temporality and contextual dimension of cultural resources. Rather than introducing a novel concept for a new cultural tourism product, the current pandemic situation allows for a critical examination of the manner in which resources are being produced. This reflection can serve as a foundation for the continued advancement of cultural resource management practices.